Associations between glycated albumin and current measures of glycaemic control in Saudi adults - Bahijri, Suhad; Sabban, Aliaa; Enani, Sumia; Alqahtani, Maha Saleh; Malibary, Manal; Alhashmi, Mohammad; Tuomileto, Jaakko (Frontiers in Endocrinology, 2026)
BackgroundCurrent dysglycaemia detection methods have limits; glycated albumin (GA), unaffected by conditions that distort HbA1c, is proposed as an alternative. We aimed to estimate the relationship between various glycaemic parameters and their association with GA in Saudi adults to evaluate GA potential utility in screening, detecting, and monitoring diabetes (DM) and intermediate hyperglycaemia (IH).MethodA total of 132 biobank serum samples (-80°C) representing a wide glycaemia range, using HbA1c, fasting plasma glucose -FPG, and 1 hour plasma glucose- 1h-PG data. Serum GA was measured by ELISA and expressed as %. Correlations with glycaemic markers were assessed, group means (normoglycaemia, IH, DM) were compared, and diagnostic performance evaluated by ROC analysis. Optimal GA cut-offs for dysglycaemia and DM were determined, with significance set at P< 0.05.ResultsUsed measures of glycaemia did not consistently classify glycaemic status in the same way. The groups with IH and DM had significantly higher mean GA values compared with the normoglycaemia group (P<0.001). GA values correlated significantly with all glycaemic markers (P<0.001), showing the strongest correlation with HbA1c, and the weakest with 1h-PG. the optimal GA cut-off values for detecting dysglycaemia was 13.9% (Sensitivity= 0.786, specificity= 0.917), and 14.7% (Sensitivity= 0.857, specificity= 0.747) for DM.ConclusionGA correlated significantly with other markers and can be suggested as an alternative to detect and monitor glycaemic status among Saudis. Further research is required to determine ranges in our population.